Enseñanza – aprendizaje de la matemática en educación básica media de la Escuela “Juan Jacobo Rousseau”. - Alomoto Guzmán, Jonathan Eduardo (2022)
The research was oriented from the following problem How to solve the learning problems presented by high school students in the subject of mathematics of the School of Basic Education "Juan Jacobo Rousseau"? and the general objective is "To implement strategies to promote the learning of mathematics in the students of secondary education of the "Juan Jacobo Rousseau" School. A mixed approach was used, descriptive applied research and inductive deductive methods, survey, observation and validation of experts, which allowed to reach the following conclusions: The different theoretical foundations of the teaching and learning process were established in order to support the variables of the research and especially in the area of mathematics; The diagnosis was made with the purpose of knowing the learning acquired by the students; The ABP methodological strategy was designed in the area of mathematics which was applied by the teacher of this educational institution, managing to improve the learning of students in the area of mathematics, which allowed greater understanding and application for and in their daily lives demonstrating the knowledge, skills and abilities, as well as the values acquired during this expendable and desired learning.